Hepatoprotective effect of chiisanoside against acetaminophen-induced acute liver injury in mice. Issue 18 (17th September 2019) - Bian, Xingbo; Wang, Shijie; Liu, Jinping; Zhao, Yan; Li, Haijun; Zhang, Lianxue; Li, Pingya
Abstract: This study was designed to investigate the hepatoprotective effect of chiisanoside (CSS) and its possible mechanisms on acetaminophen (APAP)-induced acute liver damage in mice. The serum activities of alanine transaminase (ALT), aspartate transaminase (AST), tumor necrosis factor alpha (TNF-α), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and the hepatic levels of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and malondialdehyde (MDA) were determined using the commercially available assay kits. The hepatic mRNA levels were measured by RT-PCR. The hepatic protein expressions of nuclear factor-kappa B (NF-κB), MAPK and their phosphorylated isoforms were evaluated by western blot assays. The results indicated that CSS (240 mg/kg) exhibited the hepatoprotective effects by inhibiting oxidative stress and inflammation on APAP-induced acute liver injury. Furthermore, the anti-inflammatory activity of CSS is largely related to the regulation of the NF-κB and MAPKs signaling pathways. These findings suggested that CSS possessed hepatoprotective effect against APAP-induced hepatotoxicity in mice. Abstract :